Danzhi Xiaoyao Powder Promotes Neuronal Regeneration by Downregulating Notch Signaling Pathway in the Treatment of Generalized Anxiety Disorder - Liu, Chao; Ying, Zhenhao; Li, Zifa; Zhang, Long; Li, Xin; Gong, Wenbo; Sun, Jiang; Fan, Xuejing; Yang, Ke; Wang, Xingchen; Wei, Sheng; Dong, Ning (Frontiers in Pharmacology, 2021)
Background: Generalized anxiety disorder (GAD) is one of the most common types of anxiety disorders with unclear pathogenesis. Our team's previous research found that extensive neuronal apoptosis and neuronal regeneration disorders occur in the hippocampus of GAD rats. Danzhi Xiaoyao (DZXYS) Powder can improve the anxiety behavior of rats, but its molecular mechanism is not well understood. Objective: This paper discusses whether the pathogenesis of GAD is related to the abnormal expression of Notch signal pathway, and whether the anti-anxiety effect of DZXYS promotes nerve regeneration in the hippocampus by regulating the Notch signaling pathway. Methods: The animal model of GAD was developed by the chronic restraint stress and uncertain empty bottle stimulation method. After the model was successfully established, the rats in the model preparation group were divided into the buspirone, DZXYS, DZXYS+DAPT, and model groups, and were administered the corresponding drug intervention. The changes in anxiety behavior of rats were measured by open field experiment and elevated plus-maze test, and morphological changes and regeneration of neurons in the rat hippocampus were observed by HE staining and double immunofluorescence staining. Changes in the expression of key targets of the Notch signaling pathway in the hippocampus were monitored by PCR and western blotting. Results: In this study, we verified that the GAD model was stable and reliable, and found that the key targets of the Notch signaling pathway in the hippocampus of GAD rats were significantly upregulated, leading to the increased proliferation of neural stem cells in the hippocampus and increased differentiation into astrocytes, resulting in neuronal regeneration. DZXYS intervention in GAD rats can improve appetite, promote weight growth, and significantly reverse the anxiety behavior of GAD rats, which can inhibit the upregulation of key targets of the Notch signaling pathway, promote the differentiation of neural stem cells in the hippocampus into neurons, and inhibit their differentiation into astrocytes, thus alleviating anxiety behavior. Conclusion: The occurrence of GAD is closely related to the upregulation of the Notch signaling pathway, while DZXYS can downregulate the Notch signaling pathway and promote neuronal regeneration in the hippocampus, thereby relieving anxiety behavior.